Links Between Fertility and Gender Revolution: Lithuania from a Comparative Perspective - Galdauskaitė, Dovilė (Socialinė teorija, empirija, politika ir praktika, 2021)
The study analyses trends in egalitarianism in gender role attitudes and changing associations between fertility and gender equity within and across countries and over time. Lithuania is compared to five European countries, employing an index of gender role attitudes that is constructed based on five international surveys. Findings reveal that Lithuania is not only the most traditional and slowest in transition to egalitarianism of all the countries analyzed, but also stagnating in gender revolution. The results support a U-shaped pattern between changes in fertility and gender role attitudes in almost all countries. This relationship can be moderated not only by levels of gender-equitable attitudes, but also by dispersion in attitudes and normativity of dominant gender role attitudes. The results reveal that maturation of the gender revolution can have a moderating effect.
Keywords: fertility; childbearing; gender equality; gender equity; gender roles